A historical Jesus hallucinating during his initial spirit-possession experience: A response to Stevan Da vies" interpretation of Jesus" baptism by John - Strijdom, Johan ca. 21. Jh. (Hervormde teologiese studies, 1998)
Taking Albert Schweitzer's threefold criticism of psychological readings of the historical Jesus as point of departure, Davies' analysis of Jesus' baptism is critically assessed in terms of (1) his database of sources, (2) his arguments for authenticity, and (3) his psychological explanation of this crucial event in Jesus' life. The article insists, in conclusion, that Davies, psychological analysis should be supplemented with a consideration of social values if we wish to understand the historical Jesus better.